When Home Is Loud: Strategies of Coping with Sensory Overload in Adolescents - Kalogeropoulos, Dimitra; Papadopoulos, Eleni (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore the coping strategies employed by adolescents when experiencing sensory overload in noisy and overstimulating home environments.Methods and Materials: A qualitative design was adopted to capture adolescents’ lived experiences. Twenty-five adolescents aged 13–18 years from Greece were recruited through purposive sampling. Semi-structured interviews were conducted, focusing on experiences of sensory overload, its emotional and behavioral consequences, and the strategies used to manage these challenges. Interviews continued until theoretical saturation was reached, transcribed verbatim, and analyzed using thematic analysis with NVivo 14 software. Reflexivity and peer debriefing were applied to enhance trustworthiness.Findings: Three overarching themes emerged: emotional regulation strategies, environmental and behavioral adjustments, and social and support-oriented strategies. Emotional regulation strategies included self-soothing, withdrawal, mindfulness, and cognitive reframing. Environmental and behavioral adjustments encompassed control of the physical environment, engagement in alternative activities, use of technology, and structured routines to reduce overstimulation. Social and support-oriented strategies highlighted the importance of peer validation, family understanding, professional guidance, and community engagement. While some adolescents adopted adaptive strategies such as mindfulness and family communication, others relied on avoidance or social withdrawal.Conclusion: The study underscores that adolescents employ a wide spectrum of coping mechanisms, ranging from personal regulation techniques to reliance on family and community support. Findings highlight the need for interventions that integrate individual coping skill development with family- and community-level supports.